PENGARUH POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN KARAKTER RELIGIUS ANAK DI DUSUN TEGAL SARI DESA PASIR JAYA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Fitri Alfiani; Sri Erlinda; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:this research have a background of decline of child characters. Especially the religion character of generation responsible for continuing. The first and principal place for child religion character formation is family. Therefore, the formulation of problem from this research is how the influence of parenting parents toward child religion character formation in Dusun Tegal Sari Desa Pasir Jaya Kecamatan Rambah Hilir Kabupaten Rokan Hulu. The purpose of this research is to know the influence of parenting parents toward child religion character formation in Dusun Tegal Sari Desa Pasir Jaya Kecamatan Rambah Hilir Kabupaten Rokan Hulu. The method of this research is quantitative descriptive. Data collection instrument is by using questionnaire consist of 25 questions ofparenting parents (variable X) and 43 questionsof child religion character formation (variable Y) that share to 34 muslim respondent. Analysis of data is multiple linear regression. So the hypothesis that explain “there is the influence of parenting parents toward child religion character formation in Dusun Tegal Sari Desa Pasir Jaya Kecamatan Rambah Hilir Kabupaten Rokan Hulu’ is accepted. This case is evidenced by a series of multiple linear regression test between variable X and variable Y, obtained Fcount 4,744 and Ftable 2,92, from disribution list table Ftable with N=34 at a significant level of 5%, thereby Fcount ≥ Ftable or 4,744≥2,92. Based on significant level, authoritarian parenting is not significant that is 0,496≥0,05, permissive parenting is not significantthat is 0,130≥0,05 and authoritative is significant that is 0,043≤0,05. Key Words:The Influence OfParenting parents, Religion Character